The Role of Athlete Narcissism in Moderating the Relationship Between Coaches’ Transformational Leader Behaviors and Athlete Motivation - Arthur, C.; Woodman, T.; Ong, C.; Hardy, L.; Ntoumanis, Nikos (Human Kinetics, 2011)
Leadership research that examines follower characteristics as a potential moderator of leadership effectiveness is lacking. Within Bass’s (1985) transformational leadership framework, we examined follower narcissism as a moderator of the coach behavior–coach effectiveness relationship. Youth athletes (male = 103, female = 106) from the Singapore Sports Academy (mean age = 14.28, SD = 1.40 years) completed the Differentiated Transformational Leadership Inventory (Callow, Smith, Hardy, Arthur, & Hardy, 2009), the Narcissistic Personality Inventory (Raskin & Terry, 1988), and indices of follower effort. Multilevel analyses revealed that athlete narcissism moderated the relationship between fostering acceptance of group goals and athlete effort and between high performance expectations and athlete effort. All the other transformational leader behaviors demonstrated main effects on follower effort, except for inspirational motivation.